Advanced Radio Frequency Energy Harvesting with Power Management from Multiple Sources for Low Power Sensors and Mobile Charging Applications - Sangaran M.; Ramasamy A.; Din N.M. (Electromagnetics Academy, 2023)
Energy harvesting; Low power electronics; Microstrip antennas; Microwave antennas; Motion sensors; Power management; Radio broadcasting; Radio waves; Secondary batteries; Slot antennas; Smartphones; Wi-Fi; Wireless local area networks (WLAN); Broadcast stations; Energy harvesting systems; Intermediate frequencies; Matching networks; Micro-strip patch antennas; Multiple frequency; Power management systems; Radio frequencies; Charging (batteries)